Windows XP All-in-One Desk Reference for Dummies 2nd Edition - Leonhard, Woody (Wiley Publishing, 2011)
Windows is the number one operating system in the world. There’s a lot to Windows XP, with office productivity applications, multimedia features, the Internet, and security upgrades. Now and then, you probably wish you could call Tech Support.